New insights into the dermocosmetic potential of the red seaweed Gelidium corneum - Matias, Margarida (2023)
This work addresses the potential of the red seaweed Gelidium corneum as a source of bioactive ingredients for skin health and wellness in response to the growing awareness regarding the significance of sustainable strategies in developing new nature-based dermocosmetic products. Hydroalcoholic extracts from the dried biomass were subjected to sequential liquid–liquid partitions, affording five different fractions (F1–F5). Their cosmetic potential was assessed through a set of in vitro assays concerning their antioxidant, photoprotective, and healing properties. Additionally, their cytotoxicity in HaCaT cells and their capacity to induce inflammation in RAW 264.7 cells were also evaluated. As a proof-of-concept, O/W emulsions were prepared, and emulsion stability was assessed by optical microscopy, droplet size analysis, centrifugation tests, and rheology analysis. Furthermore, in vivo tests were conducted with the final formulation to assess its antioxidant capacity. At subtoxic concentrations, the most lipophilic fraction has provided photoprotection against UV light-induced photooxidation in HaCaT cells. This was conducted together with the aqueous fraction, which also displayed healing capacities. Regarding the physical and stability assays, the best performance was achieved with the formulation containing 1% aqueous extract, which exhibited water retention and antioxidant properties in the in vivo assay. In summary, Gelidium corneum displayed itself as a potential source of bioactive ingredients with multitarget properties for dermatological use.